Rice-Blast Disease Monitoring Using Mobile App - Ramesh, S; Vydeki, D (International Journal of Engineering and Technology, 2018)
This research paper focuses on implementation of image analysis algorithms on captured images for the purpose of detecting crop diseases and monitored through Mobile App. The purpose of this research is to find out the diseases in early stage, and reduce the yield loss. The system design includes sensors, controller, image analysis algorithm, Cloud storage and mobile app. Using the USB camera, images in the farm are captured and processed by controller module. This is sent to the cloud, which can be accessed by mobile App or remote user. Various image processing algorithms were used to process the images. The results are presented in this paper.Â Â